Truth be told [large type] - Ryan, Hank Phillippi (Ryan, Hank Phillippi. Jane Ryland novel., 2015)
"Truth Be Told," part of the bestselling Jane Ryland and Jake Brogan series by Agatha, Anthony, Mary Higgins Clark, and Macavity Award-winning author Hank Phillippi Ryan, begins with tragedy: a middle-class family evicted from their suburban home. In digging up the facts on this heartbreaking story--and on other foreclosures-- reporter Ryland soon learns the truth behind a big-bucks scheme and the surprising players who will stop at nothing, including murder, to keep their goal a secret. Turns out, there's more than one way to rob a bank. Boston police detective Jake Brogan has a liar on his hands. A man has just confessed to the famous twenty-year-old Lilac Sunday killing, and while Jake's colleagues take him at his word, Jake is not so sure. But he has personal reasons for hoping they've finally solved the cold case. Financial manipulation, the terror of foreclosures, the power of numbers, the primal need for home and family and love. What happens when what you believe is true turns out to be a lie?